DETECTION AND OCCURRENCE BABESIA SPP. AND HAEMOBARTONELLA SP. IN CAT PATIENT AT PET+VET ANIMAL CLINIC, CENTRAL JAKARTA - Meila Iscahyani; Tetty Barunawati Siagian (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Blood parasites such as Babesia spp. and Haemobartonella sp. (Mycoplasma haemofelis) are important vector-borne pathogens in cats that can cause hemolytic anemia, fever, lethargy, jaundice, and systemic complications. In severe cases, these infections may lead to profound anemia, organ dysfunction, and potentially fatal outcomes, particularly in immunocompromised animals. Despite their clinical significance, epidemiological data on feline hemoparasites in Indonesia, especially in urban clinical settings, remain limited. This study aimed to detect and determine the occurrence of Babesia spp. and Haemobartonella sp. in cats examined at PET+VET Animal Clinic, Central Jakarta, and to describe their distribution based on breed, age, sex, and management practices. A total of 51 blood samples collected from December 2024 to November 2025 were examined using blood smear technique with methylene blue and eosin staining and observed under a light microscope at 1000× magnification. Fourteen samples (27.45%) were positive for blood parasites. Babesia spp. was the most prevalent (21.57%), followed by Haemobartonella sp. (3.92%) and co-infection (1.96%). Infections were more frequently observed in male, adult, domestic, and indoor-managed cats.These findings provide baseline data for improving early detection and vector control strategies in urban feline populations.